Optimal Location of a Capacitor Bank in a Primary Feeder to Load up Linearly - Hermagasantos Zein; Erwin Dermawan (Institut Teknologi Sepuluh Nopember, 2014)
A capacitor bank is not only used to improve the power factor, but also can be used to reduce losses in the power system network, such as its placement on the primary feeder. The position of the capacitor bank will be affected by the compensation factor and the sharpness of increase loads linearly in a primary feeder. This paper is aimed to determine an optimal location of the capacitor bank in the primary feeder which their loads increasing linearly in order to get maximum loss saving. Mathematical model to determine the optimal location of the capacitor bank has been clearly derived in this paper. Simulation results show that the maximum loss reduction occurs in compensation between 50% and 100%, with get loss saving about 52%. In these conditions, optimal locations lay between 75% and 100%. These results were influenced by the sharpness of the increase loads and the compensation factor. For loads increasing sharply, the position of the capacitor banks will be further away from the substation; whereas for greater compensation factor, the position of the capacitor bank will be getting closer to the substation.